Analisis Peran Pemuda dalam Ragam Organisasi pada Komite Nasional Pemuda Indonesia (KNPI) demi Mewujudkan Budaya Politik Pancasila - Azhar Hayatunnisa; Eli Apud Saepudin; Siti Apriliyaningsih; Listia Ulya Madina; Faicha Nurhasna; Siti Lita Rosita (UNIVERSITAS SERAMBI MEKKAH, 2024)
The Indonesian Youth National Committee (KNPI) is a youth organization formed on October 28, 1950. KNPI aims to foster and develop the potential of Indonesian youth, increase youth participation in national development, realize national unity and integrity. The role of youth in the organization of the Indonesian Youth National Committee (KNPI) is important in creating a political culture of Pancasila. Youth is a milestone for the progress and development of the nation, and is very often associated with the progress of a nation. The role of youth in the life of the nation and state is no doubt, since the historical struggle for Indonesian independence. The role of youth in the Indonesian national movement from 1908-1928 was also very significant, through the struggle to form a national youth organization, find a national symbol, and introduce Indonesia to the international world. In the KNPI organization, youth have an important role in creating a political culture of Pancasila, which is the basis of Indonesian law and state administration. Youth can play a role in developing leadership, building communities, and developing student affairs. Youth organizations can also be a platform to develop the skills and leadership necessary in achieving the goals of a capable society.